New workers confronting the old rules of industrial vocational education in a new era: working class experience in Alibeyköy school - Erdem, Ilgın. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
This thesis examines the material and cultural production of the working class industrial vocational education in the context of neo-liberalism and deindustrialization. My analysis claims that industrial vocational high schools have become places for only young people who have lower-class-backgrounds after the introduction of neoliberal policies and the settlement of flexibly-organized and dispersed production regime. The ethnographic research made in a single school (Alibeyköy Industrial Vocational and Technical High School) specifies the case for the search of working class experience in a marginalized neighborhood in Istanbul. As a working class residential and industrial suburb of Istanbul from 1950s to 1990s, and currently as the landscape of de-industrialization and re-organization, Alibeyköy offers an opportunity to observe the latest trends in the industrial work experience. In the school’s and the neighborhood’s current worsened position, students do not have motivation for social mobility and rather, shaped distinctive forms of cultural identification, belonging, inclusion and exclusion practices in the school space. They formed an informal counter-school culture in the school by adopting hegemonic masculinity which relied on violence, mockery and exclusionary practices. This study argues that such practices have parallels with the informal sector work relations that they had an effect in preparing the young labor force not only materially but also culturally for their future work life.
Keywords: Technical education -- Turkey.; Industrial arts -- Study and teaching.; Vocational education -- Turkey.